2004
DOI: 10.1159/000078504
|View full text |Cite
|
Sign up to set email alerts
|

Misclassification Is Likely in the Assessment of Mild Cognitive Impairment

Abstract: We estimated the relative frequency of isolated memory impairment versus isolated and comorbid impairment in executive control function (ECF). One hundred and ninety-three noninstitutionalized residents of a single Comprehensive Care Retirement Community (mean age 79.2 years) were investigated. The subjects were tested with multiple measures of memory and ECF. Test scores were standardized to minimize scaling effects. ‘Impairment’ was defined as performance ≤1.5 standard deviations below the mean for the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 24 publications
3
32
2
1
Order By: Relevance
“…As elsewhere, we found a modest advantage to weighting for predictive performance [14,43] . In this study, a 5% increase in the AUC was observed for a VCI diagnosis and an over 10% increase in the AUC was observed for survival outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…As elsewhere, we found a modest advantage to weighting for predictive performance [14,43] . In this study, a 5% increase in the AUC was observed for a VCI diagnosis and an over 10% increase in the AUC was observed for survival outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…Este hallazgo podría estar relacionado con la elevada prevalencia encontrada de diabetes e hipertensión, enfermedades crónico-degenerativas asociadas con lesiones vasculares "estratégicas" en determinados circuitos cerebrales (45) que pudieran manifestarse en problemas en la realización de funciones ejecutivas. Se ha descrito que el deterioro cognoscitivo con cambios en el control de las funciones ejecutivas es suficiente para explicar el deterioro funcional general, y que las personas con deterioro cognoscitivo amnésico tienen menor riesgo de llegar a la demencia que las que presentan problemas en el control de funciones ejecutivas (46,47). En un estudio realizado por Royall y colaboradores se describe que los cambios en el control de las funciones ejecutivas están relacionadas con las actividades instrumentales de la vida diaria y, por lo tanto, con el deterioro de la capacidad funcional (48).…”
Section: Cuadro 2 Estado De Salud De Los Adultos Mayores Estudiadosunclassified
“…One example comes from the study of Alzheimer disease. Some researchers may use clinical dementia tests as a means of diagnosing Alzheimer disease (82,83). However, not all individuals who show clinical dementia necessarily develop Alzheimer disease (82).…”
Section: Phenotype Errormentioning
confidence: 99%
“…Some researchers may use clinical dementia tests as a means of diagnosing Alzheimer disease (82,83). However, not all individuals who show clinical dementia necessarily develop Alzheimer disease (82). Another example of phenotype error is the one previously mentioned: use of the PSA test for diagnosis of male prostate cancer (14).…”
Section: Phenotype Errormentioning
confidence: 99%